KEBIJAKAN PEMERINTAH PROVINSI JAMBI KABUPATEN MERANGIN TENTANG SUKU ANAK DALAM - Riswanto Bakhtiar; Sayid Anshar; Zumiarti Zumiarti; Annisa Fitri; Rangga Prayitno (UNES Law Review, 2020)
The policy of the jambi regency provincial government regulates the ethnicity of children based on Law No. 6 of 2014 concerning Villages; Permendagri No. 52 of 2014 concerning Guidelines for the Recognition and Protection of Indigenous and Tribal Peoples; and Ministry of Social Decree Number 187 / Huk / 2018 Concerning Determination of Social Empowerment Locations for Remote Indigenous Communities in 2019. Based on these regulations the regency government has issued a program specifically for the Suku Anak Dalam (SAD), namely the Remote Welfare Development Program (PKSMT) . Where there are 5 programs that have been targeted, but of the five PKSMT programs that are running there are only 4 programs, namely: (a) Settlements, (b) Smart Houses, (c) Empowerment, (d) Health.